A core material for filling gaps in wind turbine blade plies
By designing a core material for wind power blade laying gap filling with shallow grooves and optimized S-shaped grooves, the problem that the size and shape of the core material in the prior art does not meet the requirements of different gaps is solved, and the material performance of the filling effect and filling position is improved.
Patent Information
- Application Number
- CN202420970272.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2034-05-07
AI Technical Summary
In the prior art, the core material used for filling gaps of wind power blades is relatively fixed in size and shape, which is difficult to meet different gap needs, and the infusion effect is poor, which may lead to low local filling performance.
A core material for filling gaps of wind power blade laying is designed. The core material is a rectangular body, with shallow grooves and S-shaped grooves on all four sides. The S-shaped grooves are densely changed from sparse along the length direction to optimize the resin flow and filling effect.
By optimizing the groove structure of the core material, the flow uniformity and infusion effect of the resin are improved, the material performance at the filling position is enhanced, and the product waste rate is reduced.
Smart Images

Figure CN222712901U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to a core material for wind turbine blades, in particular to a core material for filling gaps in ply layers of wind turbine blades. Background Art
[0002] Wind power generation is a clean, renewable energy source with broad application prospects. At present, the main materials used in wind turbine blade design include glass fiber, pultruded sheet, core material, etc. The core material is mainly used for the shell and web of the blade. There will be gaps between the core material and other materials in the different layer structures of the shell and web, such as between the main beam of the pultruded sheet and the core material, between the main beam of the glass fiber cloth and the core material, and between core materials of different thicknesses. The gaps should be filled with corresponding materials.
[0003] At present, the conventional method for processing the gap between blade plies is to first use a tool (such as a rubber hammer or other pressure-controlled percussion device) to gently tap or continuously apply pressure to evenly distribute the core material or other materials in the gap between blade plies and fill the gap. This process helps to improve the uniformity and stability of the internal structure. In order to further ensure the firmness and stability of the internal structure of the blade, additional filling work is required after tapping. Fill the gap with core material blocks of corresponding thickness, or directly fill with core material bevel strips. Filling core material blocks or core material bevel strips can fill the remaining gaps, increase the density of the internal structure of the blade, improve the overall strength and durability of the blade, and ensure the efficient operation of the entire blade during wind energy conversion.
[0004] There are technical solutions for core material structure in the prior art. In CN214821035U, V-shaped structural grooves are added on the basis of the original deep grooves and shallow grooves on the upper and lower surfaces of the core material. The overall shape of the groove is V-shaped, which reduces the occurrence of defects such as gaps, wrinkles, and protrusions during actual use and speeds up the diversion speed.
[0005] There are also methods for making core material bevels in the prior art. CN102562477A discloses a method for making core material bevels for wind turbine blades, which is achieved through the following steps: selecting a double-sided felt core material with a fixed width; installing the core material on a cutting machine in a fixed position; cutting the core material along a cutting line; and forming two bevels of the same size and angle. This production method can form two core materials at one time, which not only improves work efficiency but also reduces material waste.
[0006] There are also design methods for the flow channels of core materials in the prior art. CN113738603A discloses grooving in different directions on the upper and lower surfaces of the core material, which can promote the flow of resin in different directions of the core material, improve the ability of the core material to be impregnated with resin, and thereby improve the fixing and bonding performance of the core material and the reinforcing fibers. By adjusting the depth of the grooving, the resin content in the core material can be increased and the waste of resin raw materials can be avoided. Moreover, the core material in this scheme has a good flow diversion effect, and the diversion net can be omitted during use, thus avoiding residual resin due to the diversion net. At the same time, the deep grooves are opened so that the core material can be bent freely, and the applicability is strong.
[0007] Through understanding of the prior art, it is found that when using core material bevels or core material blocks to fill gaps, the size, size and shape of the core material bevels or core material blocks obtained by the manufacturing method in the prior art are relatively fixed. When filling the gaps, multiple core material bevels or core material blocks may need to be superimposed, causing the core materials to be too close and unable to adapt to different gap requirements. In addition, the deep grooves and shallow grooves of the existing core materials may affect the pouring effect or cause resin-rich conditions during the pouring process.
[0008] In addition to affecting the infusion effect, since the filling core material or the core material bevel in the prior art is mostly a pure foam flat plate, the performance after infusion is relatively low, and there may be a situation where the filling local performance is low, resulting in small performance weaknesses in the blade structure.
[0009] In addition, the core materials used for filling are mostly small pieces, and there may be missing corners or missing pieces at the edges and corners. In actual operation, it is necessary to search on site for core material blocks of suitable sizes or core material bevels for splicing and filling, which is inconvenient. Utility Model Content
[0010] (I) Purpose of the utility model
[0011] In view of the above-mentioned defects and shortcomings of the prior art, the utility model proposes a core material for filling gaps in wind turbine blade ply, which can fill gaps generated during blade plying and can also be used for smooth transition thickness differences.
[0012] (II) Technical solution
[0013] In order to achieve the purpose of this utility model, the utility model adopts the following technical solutions:
[0014] A core material for filling gaps in ply of a wind turbine blade, the core material being a cuboid, and along the length direction of the core material, the cuboid comprises an upper top surface, a lower bottom surface, two side surfaces and two end surfaces; the characteristic is that shallow grooves are provided in the four surfaces of the upper top surface, the lower bottom surface and the two side surfaces of the core material, the shallow grooves are provided in the middle position in the width direction of each surface, the shallow grooves extend along the length direction of the core material, and the shallow grooves are all linear grooves; S-shaped grooves extending along the length direction are also provided in the four surfaces of the upper top surface, the lower bottom surface and the two side surfaces;
[0015] In order to improve the pouring effect and make the resin flow more uniformly in the core material, the utility model further optimizes the S-shaped groove of the S-shaped path in the length direction. The resin flows along the length direction of the core material, and the S-shaped groove of the S-shaped path changes from dense to sparse, that is, the number of S-shaped grooves in the S-shaped path per unit length along the length direction changes from many to few; the resin first enters the flow channel part with a denser design, where the resin will encounter a certain resistance, but because the flow channel is denser, the resin flow will be relatively stable, and then the resin will gradually transition to the flow channel part with a looser design. At this stage, the resin will undergo adjustments in speed and flow direction to adapt to changes in the flow channel structure. As the resin flows upstream, the flow rate of the resin will decrease, while in the loose flow channel part, the flow resistance of the resin will decrease. Through this flow channel design method, the resin can be gradually stabilized and evenly distributed during the flow process, which helps to improve the glue pouring effect.
[0016] Preferably, along the length direction of the core material, the number of the S-shaped grooves per unit length changes from more to less.
[0017] Preferably, the width of the S-shaped groove is b, and the virtual line connecting the midpoints in the width direction of the S-shaped groove is the midline of the S-shaped groove.
[0018] The midline formula f(x) of the S-shaped groove is:
[0019]
[0020] Wherein, a is the width of the upper top surface, the lower bottom surface or the two side surfaces, h is the depth of the S-shaped groove, L is the length of the upper top surface, the lower bottom surface or the two side surfaces, η is a coefficient related to the viscosity of the resin, x is the length extending from left to right along the length direction of the upper top surface, the lower bottom surface or the two side surfaces, and x is 0-L, and α is a coefficient related to the core material; the greater the flow viscosity of the resin, the greater the value of η, and α is related to the material of the core material. The greater the roughness of the core material, the smaller the value of α. Preferably, the core material for the ply filling of the blade of the utility model should be the core material conventionally used for blades, such as PET, PVC, and HPE. The actual filling and use should be the same type as the actual large-area ply core material of the blade.
[0021] Preferably, the core material thickness can be set according to the actual gap height requirements, which can generally be 5mm. The thickness direction should be consistent with the thickness direction of the conventional core material of the blade. Shallow grooves are opened on the four surfaces of the core material, namely the top, bottom and sides, in the middle of each surface. The width of the shallow groove is 1mm. In addition, S-shaped grooves with S-shaped paths are added on the four surfaces at the same time, and the width of the S-shaped grooves is 1mm.
[0022] Preferably, glass fiber fabrics are attached to the four surfaces of the core material, namely, the top, bottom and sides, and can be bonded by adhesive, and the adhesive system is the same as the blade infusion resin system. The total weight of the glass fiber fabric should not exceed 600g / m 2 , weaving direction 0° / 90° or ±45° is available.
[0023] (III) Technical Effect
[0024] Compared with the prior art, the core material for filling the gap between plies of wind turbine blades of the utility model has the following beneficial and significant technical effects:
[0025] The utility model not only solves the problem of gaps in blade plies, but also improves the performance of local filling materials, ensures good filling effects at corresponding locations, and protects the edges and corners of the filling core material to a certain extent, reducing the product waste rate. The specific beneficial effects are as follows:
[0026] 1) Glass fiber fabrics are attached to the four sides of the core material to improve the performance of the core material at the filling position and improve the bonding effect between different materials.
[0027] 2) The core material has a processing method with shallow grooves on the four sides and an S-shaped groove with an S-shaped path. No matter from which angle the core material fills the gap, it can speed up the flow rate of the infusion resin and improve the local infusion effect.
[0028] 3) The utility model further optimizes the S-shaped grooves of the S-shaped path in the length direction. The resin flows along the length direction of the core material, and the S-shaped grooves of the S-shaped path change from dense to sparse, that is, the number of S-shaped grooves of the S-shaped path per unit length along the length direction changes from many to few. The resin first enters the densely designed flow channel part, where the resin will encounter a certain resistance, but because the flow channel is dense, the resin flow will be relatively stable. Subsequently, the resin will gradually transition to the loosely designed flow channel part. At this stage, the resin will undergo adjustments in speed and flow direction to adapt to changes in the flow channel structure. As the resin flows upstream, the flow rate of the resin will decrease, and in the loose flow channel part, the flow resistance of the resin will decrease. Through this flow channel design method, the resin can be gradually stabilized and evenly distributed during the flow process, which helps to improve the glue filling effect.
[0029] 4) The centerline formula in the utility model is related to the coefficient η of the viscosity of the resin, α related to the material of the core material, the width a of the upper top surface, the lower bottom surface or the two side surfaces, the depth h of the S-shaped groove, and the length L of the upper top surface, the lower bottom surface or the two side surfaces. The flow data of the resin in the S-shaped groove is obtained through simulation experiments, and the centerline formula is obtained by data fitting. Through the centerline formula, the curve shape of the S-shaped groove from left to right along the length direction of the core material can be designed, and the S-shaped groove can be processed according to the curve, so that the resin can be gradually stabilized and evenly distributed during the flow process, which helps to improve the glue filling effect. On different core materials, by changing different parameter values, the corresponding curve can be obtained.
[0030] 5) The surface is attached with fabric, which can protect the edges and corners of the core material to prevent it from missing or falling off.
[0031] 6) The core material is relatively thin and can be cut according to actual needs at the production site, allowing the core material to fill the gap more effectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic diagram of the overall appearance of the core material for filling the gap between plies of a wind turbine blade according to the utility model;
[0033] Figure 2 is a schematic diagram of the cutting of the core material strip, and (a)-(f) are schematic diagrams of the cutting lines set on the end surface of the core material strip.
[0034] Description of reference numerals:
[0035] Core material strip 1, shallow groove 2, V-shaped groove 3, cutting line 4. DETAILED DESCRIPTION
[0036] In order to better understand the present utility model, the content of the present utility model is further explained in conjunction with the embodiments below. In the accompanying drawings, the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The described embodiments are part of the embodiments of the present utility model, not all of them. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present utility model, and should not be understood as limitations on the present utility model. Based on the embodiments in the present utility model, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present utility model. The structure and technical solution of the present utility model are further described in detail below in conjunction with the accompanying drawings, and an embodiment of the present utility model is given.
[0037] Example 1
[0038] like Figure 1As shown, the core material 1 of the utility model is a rectangular parallelepiped. Along the length direction of the core material, the rectangular parallelepiped includes an upper top surface, a lower bottom surface, two side surfaces and two end surfaces. The upper top surface, the lower bottom surface and the two side surfaces are four surfaces arranged circumferentially along the length direction of the core material, and the two end surfaces are two surfaces at the left and right ends of the core material. Along the length direction of the core material strip 1, shallow grooves 2 are provided in the four surfaces of the upper, lower and two side surfaces, that is, the four circumferential surfaces along the length direction are all provided with shallow grooves 2, and the shallow grooves 2 are located in the middle position of the width direction of each surface. The shallow grooves are linear grooves and extend along the length direction. In this embodiment, the thickness of the core material is 5mm, and the width of the shallow grooves is 1mm. In the four surfaces of the upper, lower and two side surfaces, S-shaped grooves 3 with S-shaped paths are also provided, and the groove width of the S-shaped grooves 3 is 1mm, and the vertices of the S-shaped grooves coincide with the edges of each surface.
[0039] Along the length direction of the core material strip 1 , the S-shaped grooves of the S-shaped path change from dense to sparse, that is, the number of the S-shaped grooves of the S-shaped path per unit length along the length direction changes from many to few.
[0040] Example 2
[0041] On the basis of the core material provided in Example 1, since the S-shaped groove has a certain width, in order to realize that the S-shaped groove changes from dense to sparse along the length direction, the number of the S-shaped grooves per unit length changes from many to few along the length direction of the core material, the width of the S-shaped groove is b, and the virtual line connecting the midpoints in the width direction of the S-shaped groove is the center line of the S-shaped groove. The flow data of the resin in the S-shaped groove is obtained through simulation experiments, and the center line formula is obtained by using data fitting method.
[0042] The midline formula f(x) of the S-shaped groove is:
[0043]
[0044] Among them, a is the width of the upper top surface, the lower bottom surface or the two side surfaces, h is the depth of the S-shaped groove, L is the length of the upper top surface, the lower bottom surface or the two side surfaces, η is a coefficient related to the viscosity of the resin, x is the length extending from left to right along the length direction of the upper top surface, the lower bottom surface or the two side surfaces, and x is 0-L. α is a coefficient related to the core material; the greater the flow viscosity of the resin, the greater the value of η, α is related to the material of the core material, and the greater the roughness of the core material, the smaller the value of α.
[0045] Through the centerline formula, the curve shape of the S-shaped groove from left to right along the length direction of the core material can be designed, and the S-shaped groove can be processed according to the curve.
[0046] Example 3
[0047] On the basis of the core material provided in Example 1 or 2, glass fiber fabrics are attached to the top surface, bottom surface and two side surfaces of the core material, and can be bonded by adhesive, and the adhesive system is the same as the blade infusion resin system. The total weight of the glass fiber fabric should not exceed 600g / m 2 , weaving direction 0° / 90° or ±45° is available.
[0048] Example 4
[0049] like Figure 2 As shown, when the core material in Example 3 is used to fill the gap, the core material can be cut on site according to actual needs, and a cutting line can be set according to needs. The cutting line can be represented as a straight line or an arc on the end face of the core material strip, and the cutting line can be set along the diagonal of the end face of the core material. You can also choose any point on the upper and lower sides of the end face of the core material to connect as a cutting line. Cut the core material according to the cutting line to ensure that at least two surfaces have shallow grooves and S-shaped grooves after cutting, and the shallow grooves and S-shaped grooves of at least one of the at least two surfaces are complete, and ensure that the glass fiber fabric at one corner of the core material corner is complete.
[0050] Through the above embodiments, the purpose of the utility model is fully and effectively achieved. Those skilled in the art can understand that the utility model includes but is not limited to the contents described in the drawings and the above specific embodiments. Although the utility model has been described with respect to the most practical and preferred embodiments currently considered, it should be understood that the utility model is not limited to the disclosed embodiments, and any modification that does not deviate from the functional and structural principles of the utility model will be included in the scope of the claims.
Claims
1. A core material for filling gaps in ply of a wind turbine blade, the core material being a cuboid, and along the length direction of the core material, the cuboid comprises an upper top surface, a lower bottom surface, two side surfaces and two end surfaces; characterized in that: Shallow grooves are provided on the top surface, the bottom surface and the two side surfaces of the core material. The shallow grooves are provided in the middle of the width direction of each surface. The shallow grooves extend along the length direction of the core material. The shallow grooves are linear grooves. S-shaped grooves extending along the length direction are also provided on the top surface, the bottom surface and the two side surfaces. Along the length direction of the core material, the number of the S-shaped grooves per unit length changes from more to less, the core material thickness is 5mm, the shallow groove width is 1mm, the S-shaped groove width is 1mm, and glass fiber fabrics are attached to the top surface, bottom surface and two side surfaces of the core material.
2. The core material for filling gaps in wind turbine blade plies according to claim 1, characterized in that: The glass fiber fabric is bonded to the four surfaces by using adhesive.
3. The core material for filling gaps in wind turbine blade plies according to claim 1, characterized in that: The total weight of the glass fiber fabric does not exceed 600g / m 2 .
Citation Information
Patent Citations
Method for manufacturing oblique corners of core materials of wind power generation vanes
CN102562477A
Core material, blade and blade forming method
CN113738603A
Wind power generation blade core material
CN214821035U
Cited By
Core material for filling gaps of laying layers of wind power blades and using method of core material
CN118288577A
A core material for filling gaps in wind turbine blades and its application method
CN118288577B